121k views
4 votes
What is the solution to the equation 4x + 2( x - 3) = x - 12​

User Texelate
by
5.2k points

2 Answers

6 votes

Answer:

-6/5 (fraction)

Explanation:

Step 1: Simplify both sides of the equation.

4x+2(x−3)=x−12

4x+(2)(x)+(2)(−3)=x+−12(Distribute)

4x+2x+−6=x+−12

(4x+2x)+(−6)=x−12(Combine Like Terms)

6x+−6=x−12

6x−6=x−12

Step 2: Subtract x from both sides.

6x−6−x=x−12−x

5x−6=−12

Step 3: Add 6 to both sides.

5x−6+6=−12+6

5x=−6

Step 4: Divide both sides by 5.

5x/5 (Cross this out) = ANSWER: (-6/5)

x = -6/5

User Dima Pasko
by
4.6k points
7 votes
the answer to this is -6/5
User AConsumer
by
4.3k points